A multi-level institutional perspective of corporate social responsibility reporting: A mixed-method study. (20th August 2020) - Khan, Majid; Lockhart, James; Bathurst, Ralph
Abstract: This paper examines the institutionalisation of corporate social responsibility reporting among listed companies in Pakistan. First, we identify the influence of industry type; regulatory pressures; the presence of CSR promoting institutions; business size; and, ownership on the extent of CSR reporting. Second, we explore the managerial perceptions on CSR reporting. In so doing, the paper extends the existing literature on the debate over accountability, regulation, international standards, sustainability and the influence or otherwise of other stakeholders by exploring organisational and external institutional drivers of CSR reporting in developing countries. The quantitative content analysis of annual reports from 29 listed companies across a range of industries is used to identify the nature and scope of CSR reporting. Four annual reports from each company (2001, 2006, 2011 & 2017 – five-yearly intervals) were selected as the reporting horizon. The content analysis demonstrated considerable growth in CSR reporting, potentially enabled by various organisational and institutional factors. To explore the perceptions, motivation, and authenticity of these reports, on-site interviews with 15 managers are then conducted. The interviews highlight that public image and company recognition are the primary motivation for CSR reporting, rather than the pursuit of improved tangible outcomes. We discuss the contributions to research of institutional theory on CSR reporting and pose recommendations to both managers and regulators. Graphical abstract: Image 1 Highlights: A sample of Pakistani listed companies shows that institutional environment affects corporate social responsibility (CSR) reporting. Our results portray a significant increase in CSR reporting over the timeframe studied. We find a strongly significant impact of regulatory influences and promoting institutions on such CSR reporting. No significant relationship of explanatory variables including hazardous industries; MNC's subsidiaries; and, size exists with CSR reporting. The qualitative analysis of CSR reporting highlights issues related to reporting quality, and lack of experience, among other challenges.